Sideshow or center stage? Information transmission between CDS and equity markets - Rubesam, Alexandre; Zimmermann, Paul (Journal of Financial Intermediation, 2025)
Recent studies provide strong evidence that credit default swap (CDS) markets play a leading role in information intermediation. This paper proposes a model to rationalize the information transmission mechanism between the CDS and equity markets. In our model, informed traders with an informational advantage obtained from monitoring credit markets engage in capital structure arbitrage and trade strategically to exploit mispricings between individual stocks and CDS. In line with our model’s prediction, our empirical results provide evidence of a contemporaneous channel transmitting structural CDS shocks to equities. A positive shock to CDS decreases stock returns contemporaneously and over the long run. This credit-to-equity channel dominates the reverse transmission channel from stocks to CDS. Robustness tests confirm the role of the CDS market as a preferred venue for informed trading, independently of credit rating events or business sectors.